Sociology 345: Seminar in Comparative Race and Ethnic Relations - Olzak, Susan (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course analyzes factors that create, maintain, and diminish the salience of race and ethnic boundaries. We will examine some of the central debates surrounding the emergence, persistence, and change in racial and ethnic boundaries, nationalism, and mobilization.